PERAN STRES KERJA DALAM MEMEDIASI PENGARUH BEBAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA J4 HOTEL LEGIAN BALI - Ni Kadek Meita Juliawati; I Nengah Aristana; Ni Putu Yunik Anggreni (Universitas Triatma Mulya, 2022)
Turnover intention is the emergency of a desire to quit or leave a job. Turnover is one of the problems that arise related to human resources. Generally, employees who do turnover are caused by the distribution of workloads that are not appropriate and evenly distributed. The purpose of this study was to analyze the direct effect of workload and work stress on turnover intention, and examine the mediating role of work stress on the effect of workload on employee turnover intention at J4 Legian Bali Hotels. The population in this study amounted to 45 employees, with saturated sampling method, the type of research is quantitative research with causality associative approach. Data was collected by distributing online questionnaires (google form) and then data was analyzed by SEM-PLS. the results show that there is a positive and significant effect of workload on turnover intention, there is a positive and significant influence of workload on work stress, there is a positive and significant influence of work stress on turnover intention, and work stress partially mediates the effect of workload on turnover intention in J4 Legian Bali Hotels.